TARI PENDET MELALUI MEDIA CETAK MAJALAH BAGI SISWA KELAS XI SEKOLAH MENENGAH ATAS DI SUMATERA UTARA - Miselia - Cempaka; Martozet - Martozet (Universitas Negeri Medan, 2021)
ABSTRACT, This study aims to describe the stages of packaging and produce learning products Sibolga Coastal Sweep and Dance in the form of audio visual media based on Edmodo E-Learning for students of grade x high school (SMA) in Medan. The theories used in research topics namely packaging theory, learning, audio visual media and Edmodo E-Learning. The method used is the Research and Development (R&D) research method. The population and sample in the study are Sibolga Coastal Handkerchief Dance as research objects, for the research subjects using two students of 2015 Whip Dance Education Study Program and for product trials using 2 students / i and testing using 10 students / i Amir Hamzah Private High School Medan. Qualitative data collection techniques include field observations, interviews, documentation and literature and quantitative studies including research instruments that use questionnaires to test the feasibility of material, media and field trials. The study was conducted at the Dance Studio of Dance Education Study Program at the Department of Language and Art, Faculty of Languages and Arts, Medan State University and Amir Hamzah Medan Private High School and was conducted in July 2019 to September 2019. This study used a Likert scale to calculate the overall average in data analysis. The results of the study revealed that there were 9 stages in packaging the learning products of Sibolga Coastal Handkerchief dance material in the form of Edmodo E-Learning audio visual media for grade X high school (SMA) students in Medan consisting of (1) Potential and problems , (2) Gathering information, (3) Product design, (4) Design validation, (5) Design improvements, (6) Product trials, (7) Product revisions, (8) Product trials, (9) Product revisions. In the product validation phase, it involves 2 material expert validators and 1 media expert validator. This product gets a very good category with a detailed score of 4.6 from the material expert validation test, a 4.7 score from the media expert validation test and a 4.3 score from the student use trial. The score proves that this learning video product is very good and feasible to be applied in the process of learning Cultural Arts especially in the field of Dance Class X High School. This learning video product is packaged in the form of audio visual media that is uploaded into Edmodo E-Learning application that is used by utilizing the internet network. However, the learning video can still be used without an internet network by uploading it into a CD / DVD Room, flashdisk and so on. Keywords: Packaging, Learning Media, Printing Magazine, Pendet Dance. ABSTRAK, Penelitian ini bertujuan untuk mendeskripsikan tahapan pengemasan dan menghasilkan produk pembelajaran tari pendet dalam bentuk media cetak majalah bagi siswa/i kelas xi Sekolah Menengah Atas di Sumatera Utara. Teori-teori yang digunakan dalam topik penelitian yaitu teori pengemasan, media pembelajaran, media cetak majalah. Metode yang digunakan adalah metode penelitian kualitatif. Populasi pada penelitian adalah satu orang Mahasiswa/i Prodi Pendidikan Tari Stambuk 2015. Teknik pengumpulan data kualitatif meliputi observasi lapangan, wawancara, dokumentasi dan studi kepustakaan meliputi instrument penelitian yang menggunakan angket untuk uji kelayakan materi, media. Penelitian dilaksanakan di Studio Tari Prodi Pendidikan Tari Jurusan Sendratasik Fakultas Bahasa dan Seni Universitas Negeri Medan serta dilakukan pada Agustus 2019 hingga Oktober 2019. Penelitian ini memakai skala likert untuk menghitung rata-rata keseluruhan pada analisis data. Hasil Penelitian diketahui bahwa ada 3 tahapan dalam mengemas produk pembelajaran tari pendet dalam bentuk media cetak majalah bagi siswa/i kelas XI sekolah menengah atas di Sumatera Utara terdiri dari (1) Pra-Produksi, Menyusun ide, Wawancara, (2) Produksi, Pengumpulan data, (3) Pasca-Produksi, Tahap Editing dan Layout, Validasi Desain Produk, Revisi Desain Produk, Naik Cetak. Pada tahap validasi desain produk didapat hasil sebagai berikut :(a) Uji validasi ahli materi mendapat nilai skor sebesar 4,7 dengan kategori Sangat Baik, (b) Uji validasi ahli media mendapat nilai skor sebesar 4,8 dengan kategori Sangat Baik. Pada tahap validasi produk melibatkan 2 validator ahli materi dan 1 validator ahli media. Produk ini mendapat kategori sangat baik dengan rincian skor 4,7 dari uji validasi ahli materi, skor 4,8 dari uji validasi ahli media. Skor tersebut membuktikan bahwa produk media pembelajaran ini sangat baik dan layak untuk diterapkan dalam proses pembelajaran seni budaya khususnya bidang seni tari Kelas XI SMA.Kata kunci : Pengemasan, Media Pembelajaran Cetak Majalah Tari Pendet.